Arabia sand, sea, sky - McKinnon, Michael (London BBC Books, 1990)
The traditional Western view of the Arabian peninsula is of a forbidding monotonous region, dominated by deserts. This book aims to dispel the myth by exploring the rich natural history of the peninsula and delving into the marine worlds around its shores
1
Keywords: Ecology -- Arabian Peninsula; Ecology; Zoology -- Arabian Peninsula